From informatics to digital resources in schools: historical considerations about France - Baron, Georges-Louis (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
France was once a pioneer country in introducing information technology in education: regarding audio-visual means, the first public policies were launched in the 1950s and in the late 1960s regarding informatics. Over time, there have been rapid evolutions in technology (in particular concerning the emergence of new software), which have been difficult to manage by the system. This paper, which has mainly an historical orientation, focuses on informatics and analyzes what has happened in the domain of curriculas, a lasting prerogative of the national state. Informatics curriculas have been introduced very early in technical education (back in the 1960). Informatics has also been considered as an object of learning in secondary schools since the 1980s, with a focus on programing and algorithmics. But it has so far never been promoted to a fully fledged subject matter in general secondary education and the main idea has almost always been to use existing disciplines as a vector for it (and more widely for ICT). An interesting phenomenon has been the kind of denial of informatics as a subject of learning that appears to have won the race in secondary education, along with the rise of an interest for the development of competences. At the same time, the need for the transmission of a “digital culture” to younger generations is largely perceived. After having been very interventionist, the national administrative level has kept a responsibility of impulsion but has progressively been relayed by territorial authorities concerning concrete actions. These authorities have quickly understood the need and the possible benefits of intervening in ICT and are launching policies that sometimes interfere with the pedagogical domain: in the field of ICT, the separation between resources, teaching methods and contents may be weak. Changes may be on their way. The presentation will analyze the main phases of dissemination of ICT in French primary and secondary education and discuss some perspectives.